Mining Heritage-Based Tourism Development Management System: A Sustainable Economic Study - Muhardi, Muhardi; Oktini, Dede R. (UPT Publikasi Ilmiah UNISBA, 2024)
Through the ages, mining left behind wasteland of limited value, scarred by shafts and ponds. However, enterprising management coupled with inventive development practices, hopes to turn this legacy into a tourist boom. The primary goal of this study will tackle the planning and implementation for transforming these former mining eyesores into charming havens. The focus is on ensuring sustainable growth from these tourist hubs, all while breathing new life into these remnants of mines. Identifying pivotal facets which must be orchestrated for tourism development, this study utilized a qualitative descriptive approach towards engagement of stakeholders. The meticulously designed management system model is the analytical framework underlying this research, aimed at achieving synergistic and collaborative effort on the tourism development. In Bangka Belitung Province, the study zeroed in on Kampong Reklamasi within East Belitung Regency. The conclusion from the study show that a comprehensive developmental system is the core foundation of effective tourism development management. Such a system is founded on a mixture of creative innovation and a collaborative link between multiple stakeholders. BUMDes have the primary responsibility for successful management within the scope of fostering the tourism potential of the reclamation community. The success of BUMDes in guiding this tourism attraction not be seen in a vacuum but rather as the result of synergistic cooperation with stakeholders. Their individual contributions and roles in the development of heritage-focused tourism are a prerequisite for this collaboration. A robust and long-lasting economic framework for sustainable development is promoted by this symbiotic approach.